Structural transformation in the presence of trade and financial integration in sub-Saharan Africa - Imhotep Paul Alagidede; Muazu Ibrahim; Yakubu Awudu Sare (Central Bank Review (CBR), 2020)
This study examines the impact of trade and financial integration on structural transformation relying on data from 28 countries in sub-Saharan Africa (SSA) over the period 1985–2015. Results from our system generalized method of moments (GMM) show that, trade and financial integration significantly spur manufacturing and agricultural sector value additions. However, for the industrial sector, only financial integration robustly influences industrial growth with no effect on the service sector. Further evidence also suggests that trade and financial integration are complementary to each other and do not operate independently to influence structural transformation in SSA.
Keywords: E43; E52; G12; 330; Trade integration; Financial integration; Sectoral value additions; Structural transformation